2022
DOI: 10.3390/plants11151947
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Grafted Tomato with Drought Tolerance

Abstract: Grafting is a method used in agriculture to improve crop production and tolerance to biotic and abiotic stress. This technique is widely used in tomato, Solanum lycopersicum L.; however, the effects of grafting on changes in gene expression associated with stress tolerance in shoot apical meristem cells are still under-discovered. To clarify the effect of grafting, we performed a transcriptomic analysis between non-grafted and grafted tomatoes using the tomato variety Momotaro-scion and rootstock varieties, TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
(67 reference statements)
0
11
0
Order By: Relevance
“… 5 , 6 We previously found that Momotaro (Momo) homo-grafting, using the same species as a vigorous rootstock, and self-grafted, increased drought tolerance after 12 days of drought stress treatment. 7 While it was expected in homo-grafting, we observed that self-grafting also increased drought tolerance in Momo shoots. Several differentially expressed genes were found in the shoot apical meristem; however, the mechanism behind its activation is still unclear.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“… 5 , 6 We previously found that Momotaro (Momo) homo-grafting, using the same species as a vigorous rootstock, and self-grafted, increased drought tolerance after 12 days of drought stress treatment. 7 While it was expected in homo-grafting, we observed that self-grafting also increased drought tolerance in Momo shoots. Several differentially expressed genes were found in the shoot apical meristem; however, the mechanism behind its activation is still unclear.…”
Section: Introductionmentioning
confidence: 51%
“…Recently, similar gene expression changes were found in a homo-grafted tomato with vigorous rootstock. 7 However, self-grafting through wounding could have strengthened the root system. One mechanism of wounding or mechanical stress that induces changes in plants is thigmomorphogenesis, where the signalling pathways of phytohormones are implicated and thus may trigger potential responses to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought or high temperatures seriously affect the growth and development of crops. Plants have evolved various ways to cope with drought or high-temperature stress, including the regulation of morphology, response to cellular stress, hormone content, antioxidant content, and enzyme activity [ 1 , 15 , 19 , 23 , 24 ]. These stress responses are all based on regulation by corresponding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several transcriptome analyses have been reported to identify genes responding to dehydration stress in tomatoes [15,35], they only presented DEGs (differentially expressed genes) from the genome-wide level instead of specific groups of genes. Here, we performed genome-wide RNA sequencing of tomato leaves treated with or without dehydration, and specifically focused on differentially expressed TFs.…”
Section: Introductionmentioning
confidence: 99%